Comparative Effect Of Mulakadi Lepa & Guduchyadi Kwatha On The Symptoms Of Dadru Kushtha W.S.R. To Fungal Dermatophytes: A Randomized Clinical Trial” - Verma, Ravi Prakash; Sevatka, B K (International Research Journal of Ayurveda & Yoga, 2021)
Background: Dadru is one type of Kushtha, all skin illnesses are categorised under the broad title of ‘Kushtha′ in Ayurveda. It involves clinical features like Kandu, Deergha Pratana, Utsanna Mandala, Raga, Pidaka, which exhibit the involvement of Kapha and Pitta. Dadru correlated with ’Fungal dermatophytes through a modern perspective based on presenting symptomatology. Globally, up to 20% of the population may be infected by ringworm at any given time. Mithya Ahara-Vihar, unhygienic condition and many environmental factors lead to increase cases of Dadru. Aim:To evaluates and compares the efficacy of Guduchyadi Kwatha and Mulakadi Lepa in the management of Dadru Kushtha. Methodology: Randomized Clinical Trial on 100 patients was conducted at NIA Jaipur for the duration of 1 month equal divided in 2 Groups. Result: Statically significant improvements were showed in subjective parameters. Conclusion: it was found that average percentage of relief was higher in “Group A (Mulakadi Lepa)” (45.03%) followed by Group B Guduchyadi Kwatha (19.77%) without any serious adverse drug reaction.